Prevalence of H. pylori Infection among Patients with Chronic Gastric Symptoms and The Role of Gastric Biopsy in its Diagnosis and Management - Mabroukah Khalleefah; Yousef Hasen; Zinab Elfituri; Masoud Edeeb; Khoulah Alreeshi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Helicobacter pylori (H. pylori) infection is a common bacterial infection that affects people worldwide. It is estimated that over half of the global population is infected with H. pylori. Complications associated with H. pylori infection include dyspepsia, heartburn, and peptic ulcer disease, and many studies showed that H. pylori-positive patients have a high risk of developing gastric cancer. Therefore, it is crucial to accurately diagnose and manage H. pylori infection, particularly among patients with gastric symptoms, through effective methods such as upper gastrointestinal tract endoscopy which this study aimed to prove. Methods. Over fourteen months, 256 endoscopic biopsies from patients with gastric symptoms were included. Endoscopic abnormalities, histological diagnosis of H. pylori, and histopathological findings of gastric antrum biopsies were recorded and then analyzed using SPSS. Results. About 217 of the total patients have positive H. pylori bacterium in stained samples. Females were infected with bacteria at a rate of 65%, while males were infected at a rate of 34%. The result has shown that the age group (29-56 years old) is the most affected, accounting for 50% of all positive infected individuals. On the other hand, the study found a highly significant relationship between H. pylori infection and endoscopic abnormalities, with a p-value < 0.001. Finally, for a total of 256 endoscopic samples, the histopathological results were 43.8% for chronic gastritis and 56.2% for chronic active gastritis. Conclusion. Gastric biopsy is an invasive test that is used in the diagnosis of H. pylori bacterial infection and its associated conditions such as peptic ulcer, as well as, it can help monitor disease progression.